Perceptions of Teachers in Indonesia About Having an Exchange Program with Teachers in China - Rokhman, Ali (KnE Social Sciences, 2022)
Teaching is an important profession in a society because it is closely related to the development of a nation’s civilization. Teachers must employ professionalism in their work to prepare the young generation of the nation to be better prepared to face the future. Improving the quality and professionalism of teachers should always be a major concern of the government. One potential program to improve the quality and professionalism of teachers is through an overseas teacher exchange program. This paper discusses the prospect of a teacher exchange cooperation program between the Indonesian Government and the Chinese Government, based on the perspectives of Indonesian teachers. An internet-based survey was carried out to find out whether and why Indonesian teachers are interested in participating in this collaboration program. An interesting finding from this study was that factors related to the teachers’ interest in the program included the school’s background: teachers who came from religious-based schools tended to not accept the teacher exchange program, and have opinions that educational cooperation with the Chinese Government is not necessary. Keywords: China education system, international exchange program, teacher perception